Setting Up a Cryopreservation Programme for Immature Testicular Tissue: Lessons Learned After More Than 15 Years of Experience. (November 2019) - Braye, Aude; Tournaye, Herman; Goossens, Ellen
Young boys undergoing gonadotoxic treatments are at high risk of spermatogonial stem cell (SSC) loss and fertility problems later in life. Stem cell loss can also occur in specific genetic conditions, eg, Klinefelter syndrome (KS). Before puberty, these boys do not yet produce sperm. Hence, they cannot benefit from sperm banking. An emerging alternative is the freezing of testicular tissue aiming to preserve the SSCs for eventual autologous transplantation or in vitro maturation at adult age. Many fertility preservation programmes include cryopreservation of immature testicular tissue, although the restoration procedures are still under development. Until the end of 2018, the Universitair Ziekenhuis Brussel has frozen testicular tissues of 112 patients between 8 months and 18 years of age. Testicular tissue was removed in view of gonadotoxic cancer treatment (35%), gonadotoxic conditioning therapy for bone marrow transplantation (35%) or in boys diagnosed with KS (30%). So far, none of these boys had their testicular tissue transplanted back. This article summarizes our experience with cryopreservation of immature testicular tissue over the past 16 years (2002-2018) and describes the key issues for setting up a cryopreservation programme for immature testicular tissue as a means to safeguard the future fertility of boys at high risk of SSC loss.